SEARCHING WIDELY OR DEEPLY? THE IMPACT OF OPEN INNOVATION ON INNOVATION AND INNOVATION PERFORMANCE AMONG INDONESIAN MANUFACTURING FIRMS - Arif Hartono; Ratih Kusumawardhani (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
Since the term Open Innovation (OI) was coined by Henry Chesbrough in 2003, OI studies have been frequently conducted. Surprisingly, OI insights, in the context of Indonesian firms, are scarce. Furthermore, there are no existing OI studies that use data derived from innovation surveys. Hence, this study attempts to close the gap in the literature, by providing insights into Indonesian firms’ openness toward external knowledge, and its impact on innovation performance. The main aim of this study is to investigate the impact of OI practices on Indonesian manufacturing firms’ propensity to innovate (i.e. their product, process, organization, and marketing) and innovation performance. Product and process innovations are grouped under the term technological innovation, while organization and marketing innovations are classified as non-technological innovation. Data used in this study were derived from the Indonesia Innovation Survey (IIS) 2011 that covered the period from 2009-2010. Following Laursen and Salter’s (2006) study, OI indicators consist of external search breadth (i.e. the number of external sources or search channels that firms rely upon in their innovative activities) and depth (the extent to which firms draw deeply from the different external sources or search channels) in innovation process. Undertaking logistic and tobit regressions, this study shows that in general, both breadth and depth significantly and positively affect technological and non-technological innovation, as well as innovation performance. However, the over-search on external knowledge, measured by breadth squared and depth squared, negatively and significantly influence innovation and innovation performance. This indicates that too much external knowledge, sourced during the innovation process will diminish the return of innovation. This study also finds an indication of a complementary relationship existing between internal R&D and external knowledge; meaning that the implementation of one knowledge-sourcing strategy (either sourcing from internal R&D or external knowledge) increases the marginal returns from another. Lastly, important implications related to theoretical and innovation strategies are proposed.